Selective Myeloid Depletion of Galectin-3 Offers Protection Against Acute and Chronic Lung Injury - Humphries, Duncan C.; Mills, Ross; Dobie, Ross; Henderson, Neil C.; Sethi, Tariq; Mackinnon, Alison C. (Frontiers in Pharmacology, 2021)
Rationale: Galectin-3 (Gal-3) is an immune regulator and an important driver of fibrosis in chronic lung injury, however, its role in acute lung injury (ALI) remains unknown. Previous work has shown that global deletion of galectin-3 reduces collagen deposition in a bleomycin-induced pulmonary fibrosis model (MacKinnon et al., 2012). An inhaled Gal-3 inhibitor, GB0139, is undergoing Phase II clinical development for idiopathic pulmonary fibrosis (IPF). This work aims to elucidate the role of Gal-3 in the myeloid and mesenchymal compartment on the development of acute and chronic lung injury. Methods: LgalS3fl/fl mice were generated and crossed with mice expressing the myeloid (LysM) and mesenchymal (Pdgfrb) cre drivers to yield LysM-cre+/-/LgalS3fl/fl and Pdgfrb-cre+/-/LgalS3fl/fl mice. The response to acute (bleomycin or LPS) or chronic (bleomycin) lung injury was compared to globally deficient Gal-3-/- mice. Results: Myeloid depletion of Gal-3 led to a significant reduction in Gal-3 expression in alveolar macrophages and neutrophils and a reduction in neutrophil recruitment into the interstitium but not into the alveolar space. The reduction in interstitial neutrophils corelated with decreased levels of pulmonary inflammation following acute bleomycin and LPS administration. In addition, myeloid deletion decreased Gal-3 levels in bronchoalveolar lavage (BAL) and reduced lung fibrosis induced by chronic bleomycin. In contrast, no differences in BAL Gal-3 levels or fibrosis were observed in Pdgfrb-cre+/-/LgalS3fl/fl mice. Conclusions: Myeloid cell derived Galectin-3 drives acute and chronic lung inflammation and supports direct targeting of galectin-3 as an attractive new therapy for lung inflammation.